Alboaggregins A and B. Structure and Interaction with Human Platelets - Kowalska, Anna M.; Tan, Li; Holt, John C.; Peng, Manling; Karczewski, Jerzy; Calvete, Juan J.; Niewiarowski, Stefan (Thrombosis and Haemostasis, 1998)
Viper venoms contain a variety of platelet binding proteins including those which bind to platelet GPIb/GPIX. Most of these proteins inhibit von Willebrand factor mediated platelet agglutination. Here we report the primary structures of unique members of this family, alboaggregins A and B, isolated from Trimeresurus albolabris, which have the ability to stimulate platelet agglutination and aggregation. Four chains of alboaggregin A and two chains of alboaggregin B share a high degree of homology and all cysteines in both alboaggregins are conserved. Both alboaggregins caused similar agglutination of fixed platelets. Alboaggregin A induced platelet aggregation and release reaction with EC50 = 10 and 30 nM, respectively, which is 20-fold lower than those for alboaggregin B. These observations suggest that the dimeric structure of alboaggregin B is sufficient to mediate its binding to GPIb and induce agglutination of platelets whereas aggregation and release reaction are significantly enhanced by tetrameric structure of alboaggregin A.